Evolution of burnout syndrome in Spanish healthcare professionals during and after the COVID-19 pandemic: psychosocial variables involved - Gil-Almagro, Fernanda; Carmona-Monge, F. Javier; García-Hedrera, Fernando J.; Peñacoba-Puente, Cecilia (Frontiers in Medicine, 2025)
IntroductionEvidence shows that throughout the COVID-19 pandemic, healthcare workers have experienced high levels of burnout. The preceding literature also points to the need to consider the three elements of burnout independently, as they appear to have different evolutionary trends and possibly different buffering and amplifying variables, although these aspects have hardly been explored.MethodsThe aim of the present investigation is precisely to shed light on these latter issues. It is a prospective study, carried out in 256 healthcare workers in Spain during three time points in relation to the COVID-19 pandemic: (1) (T1) between 5 May and 21 June 2020 (final phase of the state of alarm declared in Spain on 14 March), (2) (T2) 6 months after the end of the state of alarm (January–April 2021), and (3) (T3) 1 year after this second evaluation (April–July 2022). The different components of burnout syndrome (emotional exhaustion, depersonalization and self-fulfillment) were assessed at the second and third time points. Together with sociodemographic and occupational data (age, gender, professional category, years of experience, hours of work), anxiety, depression, stress, family support, friends’ support, and self-efficacy were assessed at the first time point. At the second time point, cognitive fusion and resilience were assessed. At the third time point, optimism and hopelessness were assessed.ResultsThe results show significant decreases in burnout syndrome (p < 0.001). However, when observing the evolution of each of the dimensions, it can be seen that emotional exhaustion has significantly decreased (p < 0.001), while an increase in depersonalization (p < 0.001) and a decrease in self-fulfillment (all p < 0.001) are observed. The results of the repeated measures General Linear Models, after controlling for the effect of the covariates show that the evolution of emotional exhaustion is associated with the levels of depression at T1 (p = 0.031), of cognitive fusion at T2 (p < 0.001) and of resilience at T2 (p = 0.039). The evolution of depersonalization is associated with levels of hopelessness at T2 (p = 0.042). Finally, the evolution of self- fulfillment is associated with levels of optimism at T3 (p = 0.043) and hopelessness at T3 (p = 0.019).DiscussionThe results highlight the need to attend to the three components of burnout in a differentiated manner. Our results indicate that, during the COVID-19 pandemic, although overall burnout levels tend to decrease, it is actually emotional exhaustion that decreases, but levels of depersonalization increase and self- fulfillment decreases. In addition, the data point to the different personality factors involved in each of the dimensions. While the evolution of emotional exhaustion seems to be more affected by the levels of symptomatology (i.e., depression) at the onset of the pandemic, and of the inability to handle intrusive thoughts (i.e., cognitive fusion), the evolution of depersonalization and self- fulfillment are more related to long-term cognitive-emotional personality variables such as optimism and hopelessness.Practical implicationsThe results found have important practical implications for the prevention of each of the implicated components of the syndrome. Although further research is needed, emotional exhaustion is shown to be one of the dimensions affected in the short term and intervention programs aimed at reducing anxiety and depression at times of acute stress (onset of the COVID-19 pandemic), including thought management, seem fundamental. Depersonalization and decreased self-fulfillment do not seem to respond to the same pattern. They are shown as results of a chronification of a poor management of emotional exhaustion, and in the case of their appearance, given the variables associated with their evolution (i.e., optimism and hopelessness), therapies more focused on the meaning of existence, such as Acceptance and Commitment Therapy, could be useful.